ALDEHYDE DEHIDROGENASE LEVEL AND FATTY ACID ETHYL ESTER AS BIOCHEMICAL MARKERS PERSIST LONGER THAN ETHANOL IN WISTAR RATS AFTER CHRONIC ALCOHOL CONSUMPTION - Suaniti, Ni Made; Sudewa Djelantik, A. A. Gde; Suastika, Ketut; Mantik Astawa, Nyoman (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2010)
Alcohol consumption in human has increased from year to year in Indonesia and more recently, anincreasing number of cases of alcohol intoxication, alcoholic liver disease, and death were observed.The purpose of this experimental study was to examine the significance of two known biochemicalmarkers of alcohol given by mouth in the Wistar rats. The study design used was the “Truerandomized experimental post test only control group design". The rats were randomly distributedaccording to the experimental design and were treated daily for six weeks (chronic intake) with 5%and 20% alcohol. This study used 15 rats with 5 rats for treatment group treated with 5% alcohol, 5rats for treatment group treated with 20% alcohol, and 5 rats as control group treated with distilledwater. The biochemical markers were aldehyde dehydrogenase (ALDH) and Fatty Acid Ethyl Esters(FAEE). ALDH and FAEE were two biochemical markers of ethanol which are sensitive and specificfor alcohol consumption. The study was conducted in two phases. Initially, rats were treated orallyeveryday for six weeks with 5% and 20% alcohol, and then the blood level of ethanol, ALDH andFAEE were measured. Blood samples were collected at 6 and 24 hours after the last oral intake ofchronic alcohol administration. Qualitative analysis was carried out to detect the presence of ethanol,ALDH, and FAEE in the treatment groups and quantitative analysis to determine their levels in theblood of Wistar rats. Statistical analysis of ALDH was done by using parametric test and the presenceof FAEE persisting longer than ethanol by non-parametric test. The results showed that ALDHpersisted and increased significantly following chronic consumption of alcohol in the rats. Similarly,FAEEs persisted longer than ethanol after alcohol intake. After six hours, the ALDH level increasedby 108.14% in the rat treated chronically with 5% alcohol and by 85.07% in rat treated with 20%alcohol. After 24 hours, FAEE also persisted longer in the blood than ethanol following treatmentwith alcohol 5%. ALDH levels increased by 83.11% after chronic treatment with 5% alcohol and by112.05% in the rats treated with 20% alcohol. In the blood collected 24 hours after the last treatmentwith 5% alcohol, ALDH increased by 95.11% and by 86.79% in the rats treated with 20% alcohol.FAEE persisted longer than ethanol in the blood following administration of 5 % and 20% alcoholboth at 24 hours following chronic treatment. The longer persisting ALDH and FAEE were new andgood biochemical blood markers for chronic alcohol consumption in the Wistar rats.